The Pilgrim – Man Spends Eleven Years Walking 107,000 Kilometers in the Name of Faith (Oddity Central - Collecting Oddities, 2016)
Jose Antonio Garcia has become known as 'The Pilgrim' in his native country of Spain, after spending the last 11 years of his life walking over 100,000 kilometers to various pilgrimage sites on all continents